Effective control of filament efficiency by means of spacer HfAlOx layers and growth temperature in HfO2 based ReRAM devices. (September 2021) - Vinuesa, G.; Ossorio, O.G.; García, H.; Sahelices, B.; Castán, H.; Dueñas, S.; Kull, M.; Tarre, A.; Jogiaas, T.; Tamm, A.; Kasikov, A.; Kukli, K.
Graphical abstract: Abstract: Resistive switching random access memories are being thoroughly studied as prospective non-volatile memories. In this paper, we report electrical characterization of HfO2 :Al2 O3 based metal-insulator–metal structures devised using atomic layer deposition. Dependences of electrical behavior on HfO2 :Al2 O3 cycle ratio is studied. An explanation for the differences between the Resistive Switching properties of the samples is proposed, based on the distribution of HfAlOx layers of the sample. Dependence of the RS properties of the samples on their growth temperature is discussed.